Environmental risk disclosure practice in Malaysia: an emphasis on the plantation industry / Haslinda Yusoff … [et al.] - Yusoff, Haslinda; Darus, Faizah; Mohamed Zain, Mustaffa; Sawani, Yussri; Janggu, Tamoi (Universiti Teknologi MARA Cawangan Selangor, 2019)
This study aimed to investigate the environmental-related risk management practices via disclosures of publicly listed companies in Malaysia. A content analysis of annual and sustainability reports from 2012 to 2014 of all companies in the plantation industry was carried out. Using a disclosure rating index, the quantity and quality of the environmental-related risks disclosures was examined. The results reveal that the quantity and quality of disclosures are rather low and minimal; being in the form of short statements and a brief explanation of information. “Pollution and abatement commitment” is found to be the most disclosed category and information, followed by “environmental conservation-energy”, while, “pollution and abatement–noise outdoor” is the least disclosed one. Generally, a majority of the disclosures showed a decreasing trend. These findings indicate that typically the plantation companies in Malaysia gave minimal attention to environmental risk reporting henceforth signifying that disclosure practice is not viewed as critical to their sustainability agenda and value creation.